Peningkatan Kapasitas Pelatih Perisai Diri dalam Persiapan Kejuaraan - Asrianda; Kurniawati; Patmono Wibowo; Fadlisyah; Zulfadli (Jurnal Solusi Masyarakat (JSM), 2026)
Perisai Diri silat championships require athletes to demonstrate comprehensive readiness encompassing physical, mental, and strategic dimensions, positioning coaches as key actors in systematically directing the athlete development process. However, limited access to capacity-building programs grounded in scientific approaches remains a challenge for many coaches, particularly in managing psychological aspects, injury prevention, and the application of effective and safe training methods. This community engagement activity aims to enhance the capacity of Perisai Diri coaches in preparing athletes for competition by strengthening their understanding of psychological training, mastery of structured training methods, and the application of health and nutrition principles for athletes. The activity was implemented through integrated stages, including training sessions, mentoring, and evaluation. The results indicate a noticeable improvement in coaches’ understanding and readiness to design adaptive training programs that balance physical and mental training while giving due attention to recovery and nutritional aspects. Strengthening coaches’ capacity contributes to meeting athletes’ needs and supports sustainable improvements in performance and competitive achievement in Perisai Diri silat.